Inclusive leadership as an approach to development employees extra-role behaviour in higher education institutions: Evidence from Iraq - Salih, Raad Mahdi; Salih, Mohammed Abed; Abed, Marwan Thakir; Amanah, Ahmed Abdullah (International Journal of Management and Sustainability, 2025)
This study explores the relationship between inclusive leadership (IL) and extra-role behavior (ERB) in the context of higher education, focusing on the University of Anbar in Iraq. Given the growing challenges facing academic institutions including limited resources, increasing student populations, and the demand for innovation there is a pressing need for leadership styles that promote inclusivity, participation, and employee engagement. To address this need, the research problem was articulated through several key questions, notably: “What is the level of practicing the IL style among academic leaders in the investigated organization?” A quantitative research design was employed, and data were collected from a sample of academic leaders (n = 130) and employees (n = 480). A structured questionnaire was developed and validated to measure IL and ERB constructs. Data analysis was conducted using SPSS and AMOS v26, applying appropriate statistical techniques to test the main and sub-hypotheses. Findings indicate a significant positive relationship between inclusive leadership and extra-role behavior. These results affirm IL as a relevant and impactful leadership approach in academic settings. Limitations include its focus on a single institution, suggesting that future research should examine diverse educational and cultural settings to broaden the generalizability of the findings.